Demersal fish in the Canary Current Large Marine Ecosystem - Fernández-Peralta, Lourdes; Sidibé, Aboubacar (IOC-UNESCO, 2015)
Demersal ichthyofauna is both the most diverse and the most abundant component in terms of biomass, of the marine shelf and slope ecosystems. Within the Canary Current Large Marine Ecosystem (CCLME), Northwestern African waters hold a fish fauna even more diverse than that of Northeast Atlantic. The convergence of ichthyofaunal components of both temperate and tropical affinities results in a very biodiverse central zone, mainly in Mauritanian waters, where the transition from one faunal type to another is observed. The CCLME supports substantial demersal fish resources whose total catches decline constantly. The FAO assessments show that many important stocks are here overexploited. Species richness is minimum in waters shallower than 400 m, probably due to the heavy fishing pressure exerted over the shelf and upper slope in past decades. Conversely, deep waters are the most biodiverse, particularly between 1000 m and 1700 m depth. Northwestern African waters need to be managed both to avoid overexploitation and to ensure the protection of highly vulnerable species living on very sensitive marine ecosystems of the middle and deep continental slopes, still unexploited. A great effort of cooperation within the various actors involved in the regional fishing policies is required to ensure a sustainable management of the marine resources. Published